Ecological Social Development Model of Health Behavior of Conduct Achievement MDGs 5 - Hilmi Yumni; Fendy Suhariadi; Oedojo Sudirham; Baiq Dewi Harnani R; Hasyim As’ari; Noer Saudah (International Journal of Public Health Science (IJPHS), 2016)
Behavior of pregnant women who support the achievement of MDG 5 has not been fully achieved, one antenatal visit, shows there are still pregnant women who do not perform pregnancy tests regularly. The research aims to develop a model with Social Ecological Approach Model of Health Behavior in order to achieve the Millennium Development Goals by objective 5 with indicator of antenatal visits as well as aid delivery plan both place of birth and birth attendant. Observational study design, analytic, cross-sectional sample of 100 pregnant women who visit antenatal care at the health center Krembangan South Surabaya, simple random sampling, instruments using questionnaires, data analysis descriptive and inferential, using structural equation modeling (Structural Equation Modelling). The development of the social model of ecological models of health behavior to the behavior of the achievement of MDG 5 by the dominant factor is the construction of models intrapersonal factors include knowledge, attitude and self-efficacy, interpersonal factors include the support of family and community factors include health result support model testing goodness of fit note that the resulting model is an appropriate model used in the interpretation of the model because it has a model fit the criteria of empirical data generated by the study. The model can be used to strategize interventions in antenatal care is increasing knowledge, forming attitudes and self-efficacy through various activities such as prenatal classes or groups in pregnancy exercise as well as the involvement of family and health volunteers in assisting pregnant women to childbed.